Uma interpretação intencionalista da imagem: Percepção e comunicação visuais humanas - MOREIRA, Sylvio Allan Rocha (Universidade Federal do Pará, 2020)
The lines of investigation of human visual interactions have proposed different analytical and conceptual models, depending on the theoretical assumptions and specific objectives consistent with their focus of interest. They also have approached several aspects concerning production and reception of visual images, focusing the social aspects involved in the relations between individuals and visual images. The analysis of human visual interactions, however, also depends on ''expectations'' in reaching objectives when visually interacting with the environment. Some authors have analyzed theses expectations highlighting the concept of “intentionality” as to justify a referential property of certain mental states. They are, however, concerned mostly to human verbal interactions (e.g., verbal reading and communication) or human non-imagetic interactions (e.g., beliefs, desires, intentional actions, emotions etc.). On the other hand, the studies of human visual interactions generally use the concept of intentionality in a superficial manner, lacking an accurate conceptual treatment. The present paper aimed to evaluate the relevance of the concept of intentionality in analyzing human visual interactions, specifically, human visual perception and communication. Our objectives were: (i) to revise and present an alternative approach for the concept of intentionality; (ii) to describe historically relevant theories of human visual perception and communication, identifying their main assumptions and critics towards them; (iii) to analyze visual meaning within these theories, by adopting the categories “semantic externalism and internalism”; (iv) to analyze human visual perception and communication from the conceptual model presented in (i). We suggest that intentionality may be defined as a semantic mode of human interaction functioning that distinguishes itself from syntactic (structural and causal relations) and pragmatic (functional relations) modes of human interactions functioning. Therefore, we consider that traditional approaches of the concept of intentionality are impaired because of their attempt to reduce intentionality to syntactic and pragmatic levels of occurrence and description, instead of considering it in terms of semantic occurrence and description. Our intentionalist analysis of human visual perception distinguishes itself from traditional human visual perception theories for rejecting that perceptual meaning consists of perceptual objects: (a) apprehended in perceptual experiences (semantic internalism), or (b) functionally related to perceptual responses (externalism semantic). Alternatively, we suggest that perceptual meaning consists of “perceiving [how]”, instead of, “perceiving [what]”, becoming irrelevant to consider the existence of perceptual objects. For human visual communication, semantic analyses are impaired for admitting (i) an intrinsic or an acquired meaning to material forms of visual representation (representational hypothesis), or (ii) an intention to produce perlocutionary and illocutionary effects on audiences, by producing material forms of visual representation (communicational hypothesis). Alternatively, we suggest that visual communication means cultural-determined visual representation conditions, and visual representation means natural and cultural-determined psychological conditions (including, perceptual ones). In other words, the difficulties of coping with perceptual and communicational meaning concern of category mistakes committed by internalist and externalist semantic hypotheses of human visual perception and communication, when reducing semantic mode (intentionality) of human visual perception and communication functioning to their syntactic and pragmatic modes of functioning. An intentionalist perspective, as we have proposed in this paper, has the merit of allowing us to reconsider, firstly, the relevance of the concept of intentionality in analyzing several categories of human interactions, other than those traditionally defined as “mental states”; and, secondly, to reconsider the relevance of “meaning” in comprehending other modes of human visual interaction functioning, other than those traditionally attributed to sign systems.